(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
Blalock-Taussig Shunt provides palliation for patients with cyanotic congenital heart diseases, where an intracardiac shunting from right-to-left with inadequate pulmonary blood flow. From June (1993) to June (2015), a retrospective study was conducted on 29 patients with complex congenital cyanotic heart diseases.They underwent Blalock-Taussig Shunt at Ibn Albitar Hospital for Cardiac Surgery. Both classical (n=4) and modified Blalock-Taussig Shunts (n=25) were done. The underlying cyanotic congenital heart diseases included tetraology of fallot (n=14), transposition of great arteries (n=6), tricusp atrasia (n=3), double outlet ventricle (n=5) and pulmonary stenosis with atrial septal defect (n=1). The age of patients at the operation ranged between 2 weeks to 13 years with a mean age of 49 ± 59, and the patients’ weight ranged between 3-30 Kg with a mean weight of 11.3 ± 7.5.All shunts were performed through left or right lateral thoracotomy via fourth intercostal space. In modified Blalock-Taussig Shunts, different sizes of PTFE vascular grafts ranged between 3 to 8 mm were used . Echocardiographic studies were performed for all patients, but cardiac catheterizations were less frequently used. Shunt patency and length of satisfactory palliation for all patients were determined by different criteria. The overall mortalities were 12 patients. The majority of their deaths was related to shunt failure. Early deaths were recorded for 7 patients, 5 of them were related to shunt failure, and other 2 deaths are irrelative to shunt failure. Late deaths were 5 shunts. The overall shunt failures were 12 shunts. Most of shunt failures occurred in patients with main pulmonary artery size 6mm using graft size 6mm in modified Blalock-Taussig Shunt. In conclusions, Blalock-Taussig Shunt is good palliation for cyanotic congenital heart diseases